The interest rate, learning, and inventory investment - Louis J. Maccini; Huntley Schaller; Bartholomew Moore (The Johns Hopkins University, Department of Economics, 2004)
Economic theory predicts a negative relationship between inventories and the real interest rate, but previous empirical studies (mostly based on the older stock adjustment model) have found little evidence of such a relationship. We derive parametric tests for the role of the interest rate in specifications based on the firm's optimization problem. These Euler equation and decision rule tests mirror earlier evidence, finding little role for the interest rate. We present a simple and intuitively appealing explanation, based on regime switching in the real interest rate and learning, of why tests based on the stock adjustment model, the Euler equation, and the decision rule ?all of which emphasize short-run fluctuations in inventories and the interest rate ?are unlikely to uncover a relationship. Our analysis suggests that inventories will not respond much to short-run fluctuations in the interest rate, but they should respond to long-run movements (regime shifts; e.g., between low real rates in the 1970s and high rates in the early 1980s). Both simple and sophisticated tests confirm our predictions and show a highly significant long-run relationship between inventories and the interest rate, with an elasticity of about -1.5. Furthermore, a formal model of our explanation yields a distinctive, testable implication. This implication is supported by the data.
Keywords: E22; 330; Inventories; Interest Rates; Learning; Zins; Realzins; Lagermanagement; Kointegration; Lernprozess; Verarbeitendes Gewerbe; Schätzung; USA